Antifungal activity examination of novel acyl thioureas - Troianova, A.; Jirásková, T.; Buhaiova, V.; Cao, S.; Antypenko, L.; Sadykova, Zh.; Hassan, F.; Kholodniak, O.; Kovalenko, S.; Коваленко, Сергій Іванович; Steffens, K. (Запорізький державний медичний університет, 2018)
Namely, it was reported [1] that thiosemicarbazone i inhibited the growth of fungal strains A. nomius, A. ochraceus and A. parasiticus with a MIC of 125 μg/mL and of A. flavus and F. verticillioides with MICs of 250 μg/mL and 500 μg/mL, respectively. Pyrimidine substituted ii had antifungal properties against A. flavus, A. parasiticus and F. verticillioides only in the higher concentration of 500 μg/mL. Moreover, comparing results of the thiosemicarbazone i and other semicarbazones, sulfur instead of an oxygen atom in the structure caused the best antifungal activity. Aim: This study is to investigate antifungal activity of novel acyl derivatives of thiourea with emphasis on the influence of additional sulfur in the substances structure instead of oxygen to promote fungicidal properties. Materials and methods: The mycelial growth rate assay was used for the antifungal studies [2]. Strains of filamentous fungi were obtained from the following sources: Asperillus niger DSM 246, Fusarium fujikuroi DSM 893, Verticillium lecanii, Mucor indicus DSM 2185, Penicillium digitatum DSM 2731 - from DSMZ (Braunschweig, Germany); Fusarium oxysporum 39/1201 St. 9336 and Botrytis cinerea from the Technische Universität Berlin (Germany); Colletotrichum higginsianum MAFF 305635, originally isolated in Japan, via the Department of Biology, Friedrich-Alexander-Universität (Erlangen, Germany); Phytophtora infestans GL-1 01/14 wild strain and p-3 (4/91; R+) were kindly donated by Julius Kühn-Institut (Quedlinburg, Germany). Potato Dextrose Agar (PDA) were purchased from C. Roth (Karlsruhe, Germany). Hymexazole (98%) was obtained from Prosperity World Store (Hebei, China). 2-((Cyclopropanecarbonyl)carbamo-thioyl)hydrazine-1-carboxamide A (100%) and N-(2-carbamothioyl-hydrazine-1-carbonothioyl)-cyclopropanecarboxamide B (100%) (Fig. 1) were obtained from Zaporizhzhya State Medical University, Department of Organic and Bioorganic Chemistry (Zaporizhzhya, Ukraine). Strains were cultivated on PDA for 6 d at 25°C. Spores from each strain were gently harvested with a sterile glass rod from plate surfaces with deionized water.
Keywords: тези